Cerebellar Nuclei Neurons Show Only Small Excitatory Responses to Optogenetic Olivary Stimulation in Transgenic Mice: In Vivo and In Vitro Studies - Lu, Huo; Yang, Bo; Jaeger, Dieter (Frontiers in Neural Circuits, 2016)
To study the olivary input to the cerebellar nuclei (CN) we used optogenetic stimulation in transgenic mice expressing channelrhodopsin-2 (ChR2) in olivary neurons. We obtained in vivo extracellular Purkinje cell (PC) and CN recordings in anesthetized mice while stimulating the contralateral inferior olive (IO) with a blue laser (single pulse, 10 - 50 ms duration). Peri-stimulus histograms were constructed to show the spike rate changes after optical stimulation. Among 29 CN neurons recorded, 15 showed a decrease in spike rate of variable strength and duration, and only 1 showed a transient spiking response. These results suggest that direct olivary input to CN neurons is usually overridden by stronger Purkinje cell inhibition triggered by climbing fiber responses. To further investigate the direct input from the climbing fiber collaterals we also conducted whole cell recordings in brain slices, where we used local stimulation with blue light. Due to the expression of ChR2 in Purkinje cell axons as well as the IO in our transgenic line, strong inhibitory responses could be readily triggered with optical stimulation (13 of 15 neurons). After blocking this inhibition with GABAzine, only in 5 of 13 CN neurons weak excitatory responses were revealed. Therefore our in vitro results support the in vivo findings that the excitatory input to CN neurons from climbing fiber collaterals in adult mice is masked by the inhibition under normal conditions.